Formation of Leaders’ Reserve for Educational and Academic Organizations - A. M. Volkova; M. M. Kuzminov; O. L. Mitryakova; M. M. Rusakova; A. A. Faktorovich (Высшее образование в России)
The article presents leaders appointment and selection methodology and procedures, the results of unique studying the competencies of rectors and academic institute leaders including those that ensure effectiveness of the organization. The main attention is paid to the model of managerial competencies as a standard, compliance with which becomes the basis for inclusion in the personnel reserve, and valid evaluation tools. To create the model, a competence-based approach, tools of the national qualification system, and a sociological survey were used.Authors describe the procedure for selecting potential managers, the methodology for developing case assessment tasks, and the criteria for ensuring the objectivity of evaluating their performance.It is shown that introduction of the model made it possible to update the qualification requirements for the leaders of universities and academic institutes; to form a system of competencies diagnostics of applicants for managerial positions; to prepare recommendations for the development of professional development programs.